The Politics of Arabic Naming And Islamization In Java: Processes of Hybridization and Purification - Askuri, Askuri; Kuipers, Joel Corneal (Al-Jamiah Research Centre, 2018)
Arabic names are a component of a changing Islamic discourse in Java. If Arabic names in Java undergo change and growth, then this has implications for changes in Javanese Islam. This research demonstrates the validity of an approach that uses names as a window into Javanese culture. Drawing on a dataset of 3.7 million names analyzed diachronically across 100 years, andÂ using a quantitative method sharpened by ethnography, the analysis of names offers a new way to investigate trends that were previously often difficult to document systematically. In the past, Javanese names usually reflected social classification: santri, abangan, priyayi, or lower and upper class. However, towards the end of the twentieth century, names with class connotations were increasingly abandoned (see Kuipers and Askuri 2017). In this paper we explore further the connection between the decline of class marked names, and the rise of Arabic names. Drawing on data from Askuri (2018), we argue that although the decline of class marked names precedes the sharp rise in the use of Arabic names, the former does not seem to have caused the latter in a simple way. Our data show that in the 20th century, there were two important stages in the Arabisation of Javanese names; 1) an initial âsyntheticâ stage of one-word blended Javanese Arab names, popular from roughly 1930-1960; 2) a later stage, beginning in 1980, of 2 and 3 word names, one of which was a purified Arabic name . The conclusions have implications for an understanding of the role of hybridity and purification in Javanese Islamic modernity.Â [Nama-nama Arab merupakan salah satu komponen dari wacana Islam yang dinamis di Jawa. Jika nama-nama Arab di Jawa mengalami perubahan dan pertumbuhan, maka hal ini memiliki implikasi perubahan dalam masyarakat Islam di Jawa. Penelitian ini menunjukkan validitas pendekatan yang menggunakan nama sebagai jendela ke dalam budaya Jawa. Berdasarkan pada dataset 3,7 juta nama yang dianalisis secara diakronis sepanjang 100 tahun, dan menggunakan metode kuantitatif yang dipertajam dengan etnografi, analisis nama menawarkan cara baru untuk menyelidiki trend yang sebelumnya sering sulit untuk didokumentasikan secara sistematis.Di masa lalu, nama-nama Jawa biasanya mencerminkan klasifikasi sosial: santri, abangan, priyayi, atau kelas bawah dan atas. Namun, menjelang akhir abad ke-20, nama-nama dengan konotasi kelas semakin ditinggalkan. Dalam makalah ini kami mengeksplorasi lebih lanjut hubungan antara penurunan nama-nama yang berkonotasi kelas rendah yang ditandai dengan dan munculnya nama-nama Arab. Berdasarkan data dari Askuri (2018), kami berpendapat bahwa meskipun penurunan nama yang berkonotasi kelas rendah mendahului kenaikan yang tajam dalam penggunaan nama-nama Arab, yang pertama tampaknya tidak menyebabkan yang terakhir dengan cara yang sederhana. Data kami menunjukkan bahwa pada abad ke-20, ada dua tahapan penting dalam Arabisasi nama-nama di Jawa; 1) tahap awal âsintesisâ dari nama campuran Jawa-Arab dalam satu kata, yang populer dari sekitar 1930-1960; 2) tahap selanjutnya, dimulai pada tahun 1980, yang tersusun dari 2 atau 3 kata, dimana salah satunya ialah nama Arab yang dimurnikan (purified Arabic names). Kesimpulan ini memiliki implikasi dalam pemahaman tentang peran hibriditas dan pemurnian dalam modernitas Islam di Jawa.]